2010
DOI: 10.1039/b926364k
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced quantum yield of dendrimer-entrapped gold nanodots by a specific ion-pair association and microwave irradiation for bioimaging

Abstract: A specific ion-pair approach can be involved in precise control of the size of gold nanodots. The dendrimers with terminal amine and hydroxyl groups were a hydrophilic and hydrophobic microcavity-template, respectively, for trapping gold salts. The facile strategy can significantly enhance the quantum yield of gold nanodots from 20% to 62% after microwave irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
69
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 26 publications
0
69
0
Order By: Relevance
“…[5h] The ESI data showed a main peak at m/z = 1712, which was assigned to Pt 5 (MAA) 8 (MW = 1712.3, Figure 2) and reveals that the synthesized nanoclusters were atomically monodisperse Pt 5 . In Figure 1 a, we noticed that PAMAM (G4-OH) was eluted more slowly than the Pt nanoclusters although its molecular weight is larger than that of the latter.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5h] The ESI data showed a main peak at m/z = 1712, which was assigned to Pt 5 (MAA) 8 (MW = 1712.3, Figure 2) and reveals that the synthesized nanoclusters were atomically monodisperse Pt 5 . In Figure 1 a, we noticed that PAMAM (G4-OH) was eluted more slowly than the Pt nanoclusters although its molecular weight is larger than that of the latter.…”
mentioning
confidence: 99%
“…Shin-Ichi Tanaka, Jun Miyazaki, Dhermendra K. Tiwari, Takashi Jin,* and Yasushi Inouye* Noble-metal nanoclusters [1][2][3][4][5][6][7][8] consisting of several atoms have been gaining much attention as novel fluorescent markers [7,8] owing to their optical properties, which include size-dependent emission wavelength and discrete electronic state, features that are similar to semiconductor quantum dots. However, their smaller size and lower cytotoxicity in some ways make metal nanoclusters superior.…”
mentioning
confidence: 99%
“…Fluorescent Au NCs have been prepared mainly in a bottom-up manner by the reduction of gold precursors in the presence of various templates such as macromolecules (dendrimers [5][6][7][8][9], proteins [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], poly-butadiene [25]), small molecules (histidine [26], carbohydrate [27], thiols [28][29][30][31][32][33], N, N-dimethylformamide [34,35], penicillamine [36]), and even solid functional organisms (eggshell membrane [37]). Alternatively, top-down etching of preformed large nanoparticles down to desired NC sizes has received much attention due to many available synthetic strategies for the large nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…1f). Jao et al (2010) further reported that positively charged, dendrimer-encapsulated Au 8 NCs could penetrate the cell membrane and predominantly localized in the cytoplasm. Moreover, recent studies revealed that AuNCs also enter cells via endocytosis (Iversen et al 2011;Polavarapu et al 2011;Shang et al 2011b).…”
Section: Fluorescence Imaging Of Gold Nanoclusters In Vitromentioning
confidence: 99%